Factors influencing the success of women sports coaches: analysis of education, athletic experience, enabling factors and salary implicationsCATIONS - Aunio, Elmi (2024)
Aunio, E. 2024. Factors Influencing the Success of Women Sports Coaches: Analysis of Education, Athletic Experience, Enabling Factors and Salary Implications. Faculty of Sport and Health Sciences, University of Jyväskylä. Science of Sport Coaching and Fitness Testing, Master’s Thesis, 48 p., 1 appendix.